The Relevance of Al-Syaibany’s Thought to the Integrated Islamic School’s Integrative Curriculum: A Case Study at SMAIT Fithrah Insani - Jauhar Jundi Azkia; Syahidin Syahidin; Jenuri Jenuri (Universitas Islam Negeri Sumatera Utara, 2026)
Studies on integrative curricula in Integrated Islamic Schools have generally been dominated by research at the primary education level and literature reviews, leaving a gap in empirical analysis based on classical philosophy at the Senior High School (SMA) level. This qualitative research employing a case study method aims to evaluate the relevance of Omar Mohammad Al-Toumy Al-Syaibany’s curriculum thought at SMAIT Fithrah Insani in addressing the dichotomy between religious and general sciences. The results conclude that Al-Syaibany’s classical philosophical ideas are adaptively and vividly reflected in three main pillars: the normative aspect, which positions tawhid as an overarching worldview through cross-disciplinary assignments and structured daily religious habituation; the humanistic aspect, which recognizes students' multidimensional fitrah through holistic evaluation and academic writing autonomy; and the systemic aspect, which demonstrates a dynamic and flexible stance in responding to curriculum transitions. The primary contribution of this study provides empirical evidence that Al-Syaibany’s classical philosophy can be realistically and adaptively implemented in modern schools to address contemporary challenges. This research also enriches Islamic education curriculum studies, serves as a guideline for teachers in integrating knowledge, and offers insights for policymakers.